On the Question of the Accession of the European Union to the European Convention on Human Rights (Summary) - V. O. Ryabova (Московский журнал международного права)
The article looks at the development of the idea of accession of the European Union to the European Convention on Human Rights from its origin to the present time as well as various forms of its realization. Based on the analysis of the regulations adopted by the EU institutions and the institutions of the Council of Europe and the case-law of the Court of the EU and the European Court of Human Rights, the author comes to the conclusion about the importance of the EU accession to the ECHR as one of the steps towards the creation of unified system for the protection of human rights in Europe and the creation of joint legal environment in the EU and the Russian Federation.